Morphine Pharmacokinetics in Sickle Cell Disease: Implications for Pain Management - Darbari, Deepika S.; Neely, Michael; VandenAnker, John; Rana, Sohail R (Blood, 2009)
Abstract 2574 Poster Board II-551 Morphine is frequently used to treat pain associated with sickle cell disease (SCD) however many patients report inadequate analgesia after receiving standard doses of morphine. Little information is available on the pharmacokinetics (PK) of morphine in SCD. Morphine is metabolized in the liver by glucuronidation by the enzyme uridine diphosphate glycosyltransferase 2B7 (UGT2B7) into two major metabolites, morphine-6-glucuronide (M6G) and morphine-3-glucuronide (M3G). These metabolites are excreted by glomerular filtration. Morphine and M6G contribute to the analgesia by binding to the μ-opioid receptors. We studied morphine PK in young adults with SCD who did not have biochemical evidence of hepatic or renal involvement and were free of any acute complication of SCD. The study was approved by the Howard University Institutional Review Board. Twenty-one individuals over 18 years of age with SCD underwent 24-hour PK study of morphine. Subjects were in steady state of health and had normal serum creatinine and transaminases. All subjects reported not taking any opioid for at least one week prior to the study and were screened by urine drug screen. All participants received a single infusion of morphine sulfate (0.1 mg/kg dose, maximum 10 mg) over 30 minutes. Timed blood samples for PK parameters were drawn from an indwelling catheter and plasma was analyzed for morphine, M3G, and M6G by liquid chromatography with electrospray ionization tandem mass spectrometry. The limit of quantitation of the assay was 0.25 ng/mL for all analytes. The USCPACK software collection (http://www.lapk.org) was used to fit candidate pharmacokinetic models to the time-concentration data for morphine and each of its metabolites. Morphine pharmacokinetic parameters including AUC0-∞ (area under the time-concentration curve from dose time extrapolated to time infinity), CL (clearance), Vd (volume of distribution) and t½ (half life) were calculated in SCD subjects while non-SCD PK parameters for the general population were derived from the Duramorph® package insert. Data from 3 participants was excluded from the analysis (dosing error in one and presence of opiates in the baseline urine sample in two others). Of the remaining 18, 83% had SS phenotype and 44% were females. The mean ± SD age was 20.5 ± 3.4 years. A 3-compartment model best described disposition of morphine, while a 2-compartment model and a single compartment model were best fit for M3G, and M6G respectively. PK parameters for SCD and non-SCD population are summarized in Table 1. None of the estimated or calculated PK parameters were significantly associated with age, sex, hemoglobin concentration, serum bilirubin levels, and creatinine clearance. Table 1:Morphine pharmacokinetic parameters in SCD and non-SCD population. *Non=SCD PK parameters derived from the Duramorph® package insertParametersUnitsSCDNon-SCD *Median (Range)Typical RangesAUC0-∞ng*h/mL31.90 (27.68 – 42.51)80 – 100CLL/kg/h3.14 (2.35 – 3.61)0.9 – 1.2VdL/kg1.92 (0.96 – 3.38)1.0 – 4.7t½hours0.52 (0.27 – 0.70)1.5 – 2.0 Clearance of morphine in this cohort of young SCD adults was approximately 3-fold higher compared the non-SCD population. The mean half-life of morphine was correspondingly 3- to 10-fold shorter while the volume of distribution was within the range of the non-SCD individuals. The clearance of morphine was higher in SCD, regardless of UGT2B7 −840G>A variant status which has been shown to affect metabolism of morphine in SCD. In the absence of overt renal and hepatic involvement and acute complications of SCD, the cause for this rapid clearance is unclear but probably is due to increased metabolism/elimination of the drug since the volume of distribution in SCD was comparable to non-SCD population. While there is variability in PK parameters, increased clearance found in our study implies that in order to achieve comparable plasma levels of morphine, SCD individuals will need higher and more frequent dosing of morphine. Further investigations are needed to determine the etiology of increased clearance of morphine in SCD which may have implications in the selection of appropriate doses and frequency of morphine administration. No relevant conflicts of interest to declare.